2010
DOI: 10.4186/ej.2010.14.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Removal of H2S from Biogas by Iron (Fe3+) Doped MgO on Ceramic Honeycomb Catalyst using Double Packed Columns System

Abstract: Biogas, a clean environment fuel, is produced by anaerobic digestion of biological wastes. The presence of hydrogen sulfide (H 2 S) in biogas has a toxic and corrosive to most equipment such as piping, boilers, and powergenerating machine. H 2 S removal from biogas is of crucial importance to guarantee better performances in biogas exploitation processes, and to reduce environmental impact of gaseous emissions. Iron (Fe 3+ ) doped magnesium oxide (MgO) catalyst was synthesized using sol-gel dip coating pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Then, some of the reducing power of S 2À was consumed for reducing Fe 3þ and resulted in the inhibition of the production of hydrogen from water using S 2À as the reductant. Some researchers have reported that Fe 3þ can be reduced by S 2À during the catalytic wet oxidation of H 2 S because Fe 3þ has the potential for decomposition of H 2 S and it can be regenerated using S 2À as a reductant [30,31]. Therefore, the formation of Fe 3þ or Fe 2þ was the reason for the remarkable decrease in hydrogen production in the presence of Fe.…”
mentioning
confidence: 95%
“…Then, some of the reducing power of S 2À was consumed for reducing Fe 3þ and resulted in the inhibition of the production of hydrogen from water using S 2À as the reductant. Some researchers have reported that Fe 3þ can be reduced by S 2À during the catalytic wet oxidation of H 2 S because Fe 3þ has the potential for decomposition of H 2 S and it can be regenerated using S 2À as a reductant [30,31]. Therefore, the formation of Fe 3þ or Fe 2þ was the reason for the remarkable decrease in hydrogen production in the presence of Fe.…”
mentioning
confidence: 95%
“…The sol-gel was prepared by premixing the B solution into the A solution and stirring at room temperature for 10 minutes to form the catalyst solution. Then the C solution was added into the catalyst solution and stirred at room temperature to prepare the catalyst sol [7]. Before dip coating, the ceramic foam pieces were degreased by cleaning thoroughly and drying in an oven at 100 o C for 1 hr.…”
Section: ) Catalyst Preparationmentioning
confidence: 99%
“…Finally, the Fe 3+ doped on ceramic foam was obtained. The synthesized catalysts were characterized by Energy Dispersive X-ray Spectrometer (EDX) [7].…”
Section: ) Catalyst Preparationmentioning
confidence: 99%
“…The methane composition of microwave pretreated decanter cake in reactors R2-R9 is higher than that of the non-pretreated decanter cake in reactor R1 with the exception in the reactor R4. The percentage of methane for these experiments is lower than the typical methane percentage for anaerobic digestion (55-75% of methane) (Rakmak et al, 2010;Karellas et al, 2010). The maximum methane composition is 50.5% in reactor R6 that contains the decanter cake with 360 watts of power and 4 min of heating time using microwave pretreatment process.…”
Section: Effect Of Power and Heating Time On Bmp Testmentioning
confidence: 99%
“…The oldest of anaerobic digestion is the sewage sludge treatment (Mata-alvarez et al, 2014). Biogas is produced from the biochemical breakdown of organic substrates by microorganisms in the absence of oxygen from the anaerobic digestion (Appels et al, 2011;Vergara-Fernández et al, 2008;Brennan and Owende, 2010;Rakmak et al, 2010). Biogas is mainly composed of methane, carbon dioxide and trace gases.…”
Section: Introductionmentioning
confidence: 99%